2022
DOI: 10.1200/jco.2022.40.16_suppl.4519
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of RC48-ADC in HER2-negative patients with locally advanced or metastatic urothelial carcinoma.

Abstract: 4519 Background: RC48-ADC is a novel humanized anti-HER2 antibody-drug conjugate (ADC). A phase II clinical study showed that RC48-ADC has a good effect on locally advanced or metastatic urothelial carcinoma with HER2-positive expression that failed standard chemotherapy. In the study, some patients with HER2-postive immunohistochemistry (IHC 2+) but negative FISH test still benefited from the treatment of RC48-ADC.This study was to evaluate the activity and safety of RC48-ADC in HER2-negative patients with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 0 publications
2
19
2
Order By: Relevance
“…In this study, eight patients who received RC48 monotherapy presented an ORR of 50.0%, numerically in line with the combined outcomes of the RC48‐C005 and RC48‐C009 studies (50.5%) 17 and the RC48‐C011 study (26.3%) 16 . It exceeded the result presented by Chen et al.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, eight patients who received RC48 monotherapy presented an ORR of 50.0%, numerically in line with the combined outcomes of the RC48‐C005 and RC48‐C009 studies (50.5%) 17 and the RC48‐C011 study (26.3%) 16 . It exceeded the result presented by Chen et al.…”
Section: Discussionsupporting
confidence: 86%
“…The disease control rate (DCR) was 82.2% (95% CI: 73.7%, 89.0%), mPFS of 5.9 months (95% CI: 4.2, 7.2) and a median overall survival (mOS) of 14.2 months (95% CI: 9.7, 18.8) 17 . The RC48‐C011 study demonstrated that RC48‐ADC monotherapy achieved an ORR of 26.3% (95% CI: 9.1%, 51.2%) in la/mUC patients with low HER2 expression (IHC1+ and 0), a DCR of 94.7%, an mPFS of 5.5 months (95% CI: 3.9, 6.8), and an mOS of 16.4 months (95% CI: 7.1, 21.7) 16 . The RC48‐C014 study showed an ORR of 76.7% (95% CI: 57.7%–90.1%), an mPFS of 9.2 months, and an unreached mOS for RC48‐ADC combined with toripalimab in la/mUC patients 19 .…”
Section: Introductionmentioning
confidence: 97%
“…The preliminary result of the RC48-C011 study showed certain antitumor activity of DV in HER2-negative metastatic UC with a confirmed ORR of 26.3%, a mPFS of 5.6 months, and a mOS of 16.4 months. 27 EV and SG targets for nectin-4 and trop-2 were approved for use in the unselected patient population. In comparison, DV previously required HER2-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 19 patients were enrolled with ORR of 26.3%. Median PFS was 5.5 months, and median OS was 16.4 months 39 . These promising results encouraged investigating the synergistic efficacy of the combination of RC48-ADC with CPIs.…”
Section: Existing and Emerging Targets In Ucmentioning
confidence: 96%
“…Median PFS was 5.5 months, and median OS was 16.4 months. 39 These promising results encouraged investigating the synergistic efficacy of the combination of RC48-ADC with CPIs. In an open-label, multicenter, phase Ib/II trial (NCT04264936), the safety and the efficacy of RC48-ADC were evaluated in combination with toripalimab (anti-programmed cell death 1 antibody) in patients with metastatic UC.…”
Section: Her-2mentioning
confidence: 99%